Directly Evaluating the Optical Anisotropy of Few‐Layered Black Phosphorus during Ambient Oxidization. Issue 6 (17th January 2022) - Shen, Wanfu; Sun, Zhaoyang; Huo, Shuchun; Hu, Chunguang
Abstract: Few‐layered black phosphorus (BP) is known to be oxidized easily in the air which causes property degradation. However, the optical anisotropy of oxidized BP is yet to be well determined. Here, the optical anisotropy of the oxidized BP is revealed by continuous measurement of ambient exposed BP flake over a month using azimuth‐dependent reflectance difference microscopy. The isotropic oxidization process is elucidated by both the disappeared optical anisotropy of oxidized residuals and the unchanged crystalline orientation during BP oxidization. Unlike the severe degradation of electrical conductivity for oxidized BP within hours, the optical anisotropy is rather insensitive to the oxidization. The optical anisotropy of a oxidized BP could remain constant even days because of the isotropic optical properties and low coverage of the oxidized species at initial stage. Furthermore, when the oxidization spots grow, forming an effective layer, the oxidization layer modulates the total optical anisotropy via optical interference, which might result in an increased or decreased optical anisotropy compared with the fresh one. These results shed light on the oxidization impact on optical anisotropy and suggest a new method of manipulating optical anisotropy by controlling the degree of oxidization. Abstract : The abnormal optical anisotropy of the oxidized black phosphorus (BP) is revealed using azimuth‐dependent reflectance difference microscopy (ADRDM). Unlike severe degradation of electrical conductivity for oxidized BP within hours, the optical anisotropy of an oxidized BP could remain constant even days, and even could be increased or decreased because of the modulation by optical interference.